Chemical constituents and biological activities of calophyllum nodusum vesque and calophyllum gracilipes merr - Mad Nasir, Nadiah (2012)
The family Guttiferae includes some of the well known and important trees in Malaysia. The Calophyllum belongs to the family Guttiferae is the largest genus and locally known as ‘bitangor’. In this investigation the dried stem bark of Calophyllum nodusum and dried stem bark together with dry leaf Calophyllum gracilipes were phytochemically studied and screened for their biological activities. The stem bark of Calophyllum nodusum, stem bark and dried leaf of Calophyllum gracilipes were collected form Sabah, East Malaysia and identified by the Department of Forestry in Sandakan. The extracts were separated by various chromatographic techniques including column chromatography, chromatotron and preparative thin layer chromatography. The compounds were analysed by using MS, NMR, IR and UV techniques. Based on interpretation of these spectral data and comparison with literature reports, the structures of the new and known compounds were established. The crude extracts and pure isolated compounds from all plants were screened for free radical scavenging activity by using 1, 2-Diphenyl-2-picrylhydrayl (DPPH) assay, cytotoxic activity by tetrazolium salt (MTT) assay and antibacterial activity using disc diffusion assay. Seven compounds were isolated from the Calophyllum nodusum. From the hexane extract four known triterpenes were isolated and identified as friedelin (95), lupeol (96), stigmasterol (99) and betulinic acid (100). A new xanthone was isolated from the chloroform extract and identified as nodusuxanthone (110). Another new xanthone, trapezifolixanthone A (112) was also obtained from the methanol extract together with a known compound 4, 5-dihydroxy-2,3-dimethoxyxanthone (111). Chromatogarphic separation of the extracts of stem bark and dried leaf of Calophyllum gracilipes afforded three compounds. From the hexane stem bark and dried leaf extract, similar compounds as in the hexane extract of Calophyllum nodusum were isolated. From the chloroform stem bark extract, two known compounds were isolated and identified as zeyloxanthanone (93) and trapezifolixanthone (79). Similar chromatographic separation procedure for the methanol extract of dried leaf led to a new xanthone, gracixanthone (113). The free radical scavenging activity of the plant extracts and pure isolated compounds were carried out using 1, 2-diphenyl-2-picrylhydrayl (DPPH). However, none of the crude extracts of both plant species gave positive test results while theM methanol extracts of Calophyllum nodusum showed moderate activity (IC50 < 182.86 μg/mL). Similarly, all the compounds also displayed negative scavenging activity on DPPH assay. One of the isolated compounds, zeyloxanthanone (93) exhibited excellent cytotoxic activity against four cell lines, human prostate (PC-3), colon (HCT-116), breast (MCF-7) and mouse Macrophages (RAW 264.7) cells with IC50 values ranging from 3.6-4.5 μM. The results for the antimicrobial tests using disc diffusion assay indicated that the methanol extract of Calophyllum nodusum showed 3 mm inhbition zone against Salmonella typhimurium bacteria and the chloroform extract of Calophyllum gracilipes showed 2 mm and 2 mm inihibition zone towards Salmonella typhimurium and Escherichia coli bacteria respectively. The disc diffusion assay was further tested on isolated compounds. Trapezifolixanthone A (112) showed moderate inhibition activity towards Staphylococcus bacteria with 4 mm inhibition zone and moderate activity against Salmonella typhimurium with 5 mm. Both trapezifolixanthone (79) and zeyloxanthonone (93) exhibited medium inhibition activity against some of the microbes tested.